Inferring Personalized and Race-Specific Causal Effects of Genomic Aberrations on Gleason Scores: A Deep Latent Variable Model - Chen, Zhong; Edwards, Andrea; Hicks, Chindo; Zhang, Kun (Frontiers in Oncology, 2020)
Extensive research has examined socioeconomic factors influencing prostate cancer (PCa) disparities. However, to what extent molecular and genetic mechanisms may also contribute to these inequalities still remains elusive. Although various in vitro, in vivo, and population studies have originated to address this issue, they are often very costly and time consuming by nature. In this work, we attempt to explore this problem by a preliminary study, where a joint deep latent variable model is proposed to in silico quantify the personalized and race-specific effects that a genomic aberration may exert on the Gleason Score (GS) of each individual PCa patient. The core of the proposed model is a deep variational auto-encoder framework, which follows the causal structure of inference with proxies. Extensive experimental results on TCGA 270 European-American and 43 African-American PCa patients demonstrate that ERG fusions, somatic mutations in SPOP and ATM, and CNAs in ERG are the statistically significant genomic factors across all low-, intermediate- and high-grade PCa that may explain the disparities between these two groups. Moreover, compared to a state-of-the-art deep inference method, our proposed method achieves much higher precision in casual effect inference in terms of the impact of a studied genomic aberration on GS. Further assessment of the genomic-risk scores along with corresponding confidence intervals not only validates our results, but also provides valuable insight to the observed racial disparity between these two groups regarding PCa metastasis. The pinpointed significant genomic factors may shed light on molecular mechanism of cancer disparities in PCa and warrant further investigation.